Drugging PI3K in cancer: refining targets and therapeutic strategies. (August 2015) - Yap, Timothy A; Bjerke, Lynn; Clarke, Paul A; Workman, Paul
Highlights: PI3K is an important target for innovative anticancer drug development and precision medicine. Over 30 small molecule PI3K inhibitors are currently in clinical trial testing. These drugs include dual PI3K/mTOR, pan-Class I PI3K and isoform-selective PI3K inhibitors. The PI3Kδ inhibitor idelalisib has received FDA approval for the treatment of B-cell malignancies. Drug resistance, patient selection and development of targeted combinations remain challenges. Abstract : The phosphatidylinositol-3 kinase (PI3K) pathway is one of the most frequently activated pathogenic signalling routes in human cancers, making it a rational and important target for innovative anticancer drug development and precision medicine. The three main classes of PI3K inhibitors currently in clinical testing comprise dual pan-Class I PI3K/mTOR inhibitors, pan-Class I PI3K inhibitors lacking significant mTOR activity and isoform-selective PI3K inhibitors. A major step forward in recent years is the progression of over 30 small molecule PI3K inhibitors into clinical trials and the first regulatory approval of the PI3Kδ inhibitor idelalisib for multiple B-cell malignancies. This review article focuses on the progress made in the discovery and development of novel PI3K inhibitors, with an emphasis on antitumour activity and tolerability profiles for agents that have entered clinical trials. We also discuss the key issues of drug resistance, patient selection approaches and rational targeted combinations. Finally, we envision the future development and use of PI3K inhibitors for the treatment of patients with a range of malignancies.